Pendampingan Identifikasi Kebutuhan dan Kelayakan Usaha Badan Usaha Milik Desa di Desa Manamas Kecamatan Naibenu, Kabupaten Timor Tengah Utara - Anggelina Delviana Klau; Natalia Lily Babulu; Fredirikus Timo (LPPM Politeknik Piksi Ganesha, 2025)
It is hoped that the existence of BUMDes will become a stepping stone in efforts to increase village economic independence. It is hoped that the presence of BUMDes can result in a transformation that will raise the standard of living and welfare of the community. The journey to establish BUMDes faced a number of challenges, including internal problems that emerged within BUMDes itself. Even though it was initially planned as the main initiator of the village economy, many BUMDes ultimately failed, even becoming empty names before truly developing. The purpose of this service is to provide assistance regarding (1) identifying BUMDES business needs and (2) analyzing the feasibility of BUMDES businesses